Modelling and simulation of the performance analysis for peltier module and seebeck module using MATLAB/Simulink - K.N. Khamil,; M.F.M. Sabria,; A.M. Yusop,; R. Mohamed,; M.S.Sharuddin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Currently, the technologies used in power generation are not fully optimised and inefficient. The waste energy produced from the machines, systems and the infrastructure have created interest in energy harvesting researches especially the world is entering the Industrial Revolution 4.0 (IR4.0). This paper investigates the analytical modelling for both Peltier and Seebeck module in terms of the main parameters needed for quick evaluation depending on user’s application such voltage, current, coefficient of performance and the efficiency, thermal resistivity, total internal resistance, and Seebeck coefficient of the module. These parameters are normally given by manufacturer of the module through the datasheet. MATLAB/Simulink was used to simulate from the base equations. Graph representation of the output can be generated using several codes on Matlab command window. The simulation was tested on TEP1-1994-3.5 and TES1-05350 where the results obtained agrees well with the datasheet provided by the manufacturer which proved the MATLAB/Simulink’s modelling. The real experiment data using Peltier Module, APH-127-10-25-S proved the analytical modelling with the percentage error between simulation real experiments of 0.45% where the analytical simulation estimates the voltage output is 1.6340 V while the experimental voltage output from the in-lab experiment is 1.6266 V at hot temperature of 61°C and cold temperature of 27.5°C.